Strength characteristic of recycled concrete aggregate as an alternative material for rammed aggregate pier - Punzalan, Aivan Dredd B.; Jarcia, Fritz John O.; Torio-Kaimo, Lestelle V.; Acacio, Alexis A. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Rammed Aggregate Piers (RAP) is a cost-efficient ground improvement method that improves various types of soils. RAPs, as the name suggest, are made up of natural aggregates densified using vibratory methods. In the Philippine setting, the increasing number of construction projects around the archipelago increases the volume of produced construction and demolition (C&D) wastes, with recycled concrete aggregates (RCA) as the leading C&D waste by volume. In this study, RCA samples were investigated as alternative material for RAPs in terms of its friction angle at specified densities of 50% and 70% of the maximum dry density. RCA samples were subjected to stress-controlled Large Direct Shear Tests to determine the peak shear stresses and corresponding friction angles. Friction angles were computed using the conventional Mohr-Coulomb Method with and without cohesion, and an alternative Zero Dilation Angle Method as proposed by the Federal Highway Administration. Using the MC Method with virtual cohesion, the empirical value of friction angle of RAP is 46 degrees, and based on the experimental results, at 70% MDD, the RCA friction angle of 36.79 degrees does not meet the baseline requirement. Alternative values, calculated from MC Method without cohesion and from Zero Dilation Angle Method, yielded friction angles greater than the empirical value, however, baseline values using these alternative methods must be calculated using natural aggregates.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Aggregates (Building materials); Rammed Aggregate Piers (RAP).